DAMPAK EKSPLOITASI SUMBERDAYA ALAM KELAUTAN DAN PERIKANAN TERHADAP (KONDISI) SOSIAL EKONOMI MASYARAKAT THE IMPACT OF MARINE NATURAL RESOURCES AND FISHERIES EXPLOITATION TOWARD SOCIAL ECONOMIC ASPECTS OF THE SOCIETY - Tonny D Pariela (Pattimura University, 2020)
Exploitation of natural resources including marine and fisheries could potentially cause significant (positive and/or negative) impacts in the lives of local communities and its surrounding. Indeed, the ideal goal is to contribute to the efforts in increasing the welfare of the community; although it is often difficult to avoid the negative impact especially toward the social order. It is commonly known that natural resources are generally found in rural areas where the community used to be characterized by what commonly called Gemeinschaft. The inclusion of money capitalism through various activities of exploitation of natural resources including, let’s say for an example, what will be done in Masela block, will change the social order of society which in turn will be reflected in the way of thought and behavior of both individuals as well as groups of people. In order for community not to experiencing alienation, it is necessary to develop an idea of social safety net in order to strengthening the position and the role of the community mentioned above vis a vis other groups of people which living together or side by side in the area of exploitation and its surrounding